Evaluating the Effects of HiPhorius Phytase Added in Diets at or Below the P Requirement on Nursery Pig Growth Performance and Bone Mineralization - Macie E. Reeb; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jon R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 297 pigs (DNA 241 × 600; initially 8.64 ± 0.181 kg) were used in a 21-d trial to determine the effects of HiPhorius phytase on growth performance and bone characteristics. Pens of pigs were assigned to 1 of 5 treatments in a randomized complete block design with 5 pigs per pen and 12 replications per treatment. The first three diets were formulated to contain 0.09% aP; without added phytase (control), or the control diet with 600 or 1,000 FYT/kg of added phytase (considering a release of 0.15 or 0.18% aP, respectively). The remaining two diets were formulated to contain 0.27% aP, one without added phytase and the other with 1,000 FYT/kg. From d 0 to 21, pigs fed diets with increasing phytase containing 0.09% aP had increased (linear P ≤ 0.002) ADG, ADFI, and better F/G but phytase added to the 0.27% aP diet did not impact growth performance. Increasing phytase in diets containing 0.09% aP increased percentage bone ash in metacarpals and 10th ribs (linear,P<0.001; quadratic,P= 0.004, respectively), and increased grams of Ca and P in all three bones (linear,P≤ 0.027). An increase in percentage bone ash (P≤ 0.038) and increased grams of Ca and P in fibulas and 10th ribs (P≤ 0.023) was observed when adding 1,000 FYT/kg phytase in diets with 0.27% aP compared with pigs fed 0.27% aP without added phytase. Increasing aP from 0.09% to 0.27% in diets without added phytase increased (P<0.001) ADG, ADFI, and improved F/G. Increasing aP from 0.09% to 0.27% in diets without added phytase increased bone density (P≤ 0.002) in fibulas and metacarpals, percentage bone ash in all bones (P≤ 0.074), and increased (P<0.05) grams of Ca and P in fibulas and 10th ribs. Pigs fed diets containing 0.27% aP with 1,000 FYT phytase had increased ADFI (P≤ 0.047), bone density (P≤ 0.008) in fibulas and metacarpals, percentage bone ash in all bones (P≤ 0.002), and increased (P<0.05) grams of Ca and P in fibulas and 10th ribs compared to those fed 0.09% aP with 1,000 FYT phytase. For growth performance (average of ADG and F/G), aP release was calculated to be 0.170% for diets with 600 FYT/kg and 0.206% for 1,000 FYT/kg. For the average of all bone measurements (average of 3 bones for bone density and percentage bone ash), aP release was calculated to be 0.120 and 0.125% for diets with 600 and 1,000 FYT/kg, respectively. In conclusion, increasing phytase in diets formulated with less than the pig’s phosphorus requirement improved growth performance and bone mineralization. These data help to confirm the efficacy of HiPhorius phytase in making P more available in aP deficient diets, resulting in improved growth performance and bone mineralization. Furthermore, these data show that adding high levels of phytase in diets adequate in aP did not further improve growth performance, but increased bone mineralization.
Keywords: bone mineralization; nursery pigs; phytase; phosphorus